Institutional Economics, Social Dilemmas, and the Complexity‐Sustainability Trade‐off (A response to Hielscher and Pies). (28th March 2016) - Valentinov, Vladislav; Chatalova, Lioudmila
Abstract : Drawing inspiration from Niklas Luhmann's social systems theory, the present note argues that the complexity of social systems has the potential to undermine their sustainability and thus to generate social dilemmas. The conceptual construct of the 'complexity‐sustainability trade‐off' is invoked to make the point that ensuring sustainability, if at all possible, requires controlling the proliferation of systemic complexity. To some extent, this control is feasible through structural couplings that correspond to the economic concept of the internalization of externalities. If this solution falls short of meeting the sustainability goals, systemic complexity can be alternatively controlled through the dampening of systemic imperatives, which translates, at the individual level, into the weakening of incentives. Williamson's transaction cost theory of for‐profit hierarchy and Hansmann's trustworthiness theory of nonprofit organizations present cases in point.